Takhrij and Syarah Hadith of Agrotechnology: Benefits of Aloe Vera Plants - Intan Nur Khasanah; Wahyudin Darmalaksana; Esty Puri Utami (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the benefits of the aloe vera plant. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this study are the health benefits of aloe vera plants. The conclusion of this research is that the aloe vera plant is based on takhrij and syarah hadith which is suitable to be used as a cure for diseases and for beauty.